2022
DOI: 10.1002/smll.202201135
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne Electrochemistry: Progress and Perspectives

Abstract: Graphdiyne, a carbon allotrope, was synthesized in 2010 for the first time. It consists of two acetylene bonds between adjacent benzene rings. Graphdiyne and its composites thus exhibit ultrahigh intrinsic electrochemical activities. As “star” electrode materials, they have been utilized for various electrochemical applications. With the aim of giving a full screen of graphdiyne electrochemistry, this review starts from the history of graphdiyne materials, followed by their structural and electrochemical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 224 publications
0
28
0
Order By: Relevance
“…Graphdiyne (GDY) is a kind of two-dimensional (2D) carbon material with sp- and sp 2 -hybridized carbon atoms. It has been reported that GDY is a semiconductor material with a natural band gap of 0.44–1.47 eV while possessing a high carrier mobility of 10 4 to 10 5 cm 2 ·V –1 ·s –1 at room temperature. At the same time, its unique chemical structure, that is, diacetylenic linkages (−CC–CC−), well-distributed pores, and large π-conjugated system, endows GDY extensive application prospects in many fields such as catalysis, , energy storage and conversion, , photoelectrical device, and biomedicine. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphdiyne (GDY) is a kind of two-dimensional (2D) carbon material with sp- and sp 2 -hybridized carbon atoms. It has been reported that GDY is a semiconductor material with a natural band gap of 0.44–1.47 eV while possessing a high carrier mobility of 10 4 to 10 5 cm 2 ·V –1 ·s –1 at room temperature. At the same time, its unique chemical structure, that is, diacetylenic linkages (−CC–CC−), well-distributed pores, and large π-conjugated system, endows GDY extensive application prospects in many fields such as catalysis, , energy storage and conversion, , photoelectrical device, and biomedicine. …”
mentioning
confidence: 99%
“…It has been reported that GDY is a semiconductor material with a natural band gap of 0.44− 1.47 eV while possessing a high carrier mobility of 10 4 to 10 5 cm 2 •V −1 •s −1 at room temperature. 1−3 At the same time, its unique chemical structure, that is, diacetylenic linkages (−C� C−C�C−), well-distributed pores, and large π-conjugated system, endows GDY extensive application prospects in many fields such as catalysis, 4,5 energy storage and conversion, 6,7 photoelectrical device, 8 and biomedicine. 9−12 Since the successful preparation of GDY in 2010, 13 great efforts have been devoted into the controlled synthesis of GDY.…”
mentioning
confidence: 99%
“…They have exceeded the deficits of graphene due to different kinds of hybridization and versatile morphological configurations. [1][2][3] Depending upon structural symmetry, the derivatives of graphene are divided mainly into two categories, namely hexagonal and non-hexagonal allotropes. Earlier, it was believed that perfect hexagonal symmetry was necessary for the presence of Dirac cones in band structure.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging 2D carbon nanomaterial consisting of layers of sp and sp 2 hybridized carbon atoms, graphdiyne (GDY) is drawing increasing interest because of its attractive properties and broad-range promising applications. In particular, rich conjugated acetylenic bonds and numerous uniform in-plane cavities endow GDY with fascinating chemical/electrochemical properties and potential applications in electrochemical energy storage. It has been reported that GDY is more lithiophilic than other sp 2 hybridized carbon materials due to the rich sp-hybridization carbons, which is beneficial for the nucleation process of Li plating. , Particularly, the 18C-hexagon with sp-hybridization carbons has a lower adsorption energy for Li atoms compared with the 6C-hexagon in the sp 2 -hybridization carbon materials . Furthermore, GDY with intrinsic nanopores can act as a stable nanosieve to improve the Li + migration and optimize its deposition. , Consequently, GDY has been considered as a promising lithiophilic material to stabilize lithium metal anodes.…”
Section: Introductionmentioning
confidence: 99%